Analisis Persepsi Pengguna Jalan terhadap Penerapan Sistem Satu Arah: Studi Kasus Jalan Nani Wartabone, Gorontalo - Ahmad, Noor Fatmawanti; Abas, Mohamad Ilyas (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Traffic congestion in educational areas is a persistent issue in medium-sized Indonesian cities, including Gorontalo. JalanNani Wartabone, adjacent to Gorontalo State University, frequently experiences congestion due to student mobility,vehicle flow, pedestrians, and street vendors. To mitigate this, the city government introduced a one-way traffic system, yetits effectiveness from users’ perspectives has not been fully evaluated. This study examines road user perceptions acrossfive dimensions: comfort, safety, efficiency, accessibility, and satisfaction. Data were collected from 200 respondents(students, pedestrians, drivers, vendors) using questionnaires and analyzed with SPSS through descriptive statistics, crosstabulations, and correlation analysis, complemented by spatial heatmaps from geotagged feedback. Results revealsignificant group differences: students and pedestrians perceived positive effects in traffic order and walkability, whiledrivers and vendors reported reduced accessibility and longer travel times. The study contributes a user-centered,evidence-based framework for inclusive traffic policy in secondary cities